PARIWISATA BERBASIS MASYARAKAT (COMMUNITY BASED TOURISM) DALAM PENGELOLAAN DESA WISATA (STUDI KASUS DESA BLEBERAN KECAMATAN PLAYEN KABUPATEN GUNUNGKIDUL) - Andjar Asmara, Sebening; Padmaningrum, Dwiningtyas; Sugihardjo, Sugihardjo (SIWAYANG Journal: Publikasi Ilmiah Bidang Pariwisata, Kebudayaan, dan Antropologi, 2023)
Bleberan Village is a tourist village developed by the Bleberan Village Government by carrying the concept of community-based tourism. This study aims to determine the management of community-based tourism in Bleberan Village and its impact on the dimensions of community life in Bleberan Village. The research approach used is qualitative with a case study method. Data collection methods include participatory observation, in-depth interviews, and documentation studies. Determination of informants using purposive sampling and snowball sampling techniques. Data analysis uses an interactive data analysis model. Data validity uses source triangulation. Based on the results of the research that has been carried out, it was concluded that the management of community-based tourism in Bleberan Village has been running quite well by referring to aspects of tourism management (attraction, accessibility, amenities, ancillary), principles of tourism development (social, economic, cultural, environmental, and political principles), and promotional efforts made. However, there are still many shortcomings, namely in facilities and infrastructure and facilities such as damaged road signs, the absence of vehicle rentals for tourists. Bleberan Tourism Village has also not collaborated with travel agents, and many souvenir craftsmen have not resumed production. Promotion efforts have not been intensified again. Efforts and support from various parties are needed, especially stakeholders, so that sustainable impacts are created in aspects of community life, namely in the social, economic, cultural, environmental, and political dimensions.